Short-term cold-water immersion does not alter neuromuscular fatigue development during high-intensity intermittent exercise - Faricier, Robin; Haeberlé, Olivier; Lemire, Marcel (Frontiers in Physiology, 2023)
Aims: Pre-exercise cold-water immersion affects physical performance under ambient environment, however the mechanisms leading to this decrease remains to be elucidated. To determine whether short-term lower-body immersion in cold water could induce acute changes in the development of neuromuscular fatigue after high-intensity exercise. Methods: Ten participants performed on two separate visits a fatigue task (60 intermittent isometric maximal voluntary contractions maintained over 3 seconds and spaced by 2 seconds of recovery) once after lower-body cold-water immersion (Pre-Cooling, 6 minutes at 8.9 ± 1.6 °C) and another time without prior immersion (Control). Before and after the fatigue task, neuromuscular function was assessed during voluntary or evoked contractions (electrical stimulation performed on the femoral nerve) on contracted and relaxed on knee extensor muscles. Results: No differences in neuromuscular fatigue were measured between Pre-Cooling and Control conditions, despite maximal voluntary contraction reductions (-49 and -48%, respectively, both p < 0.05), peripheral contractile capacities (both -28%, p < 0.05). Additionally, rate of perceived exhaustion increases over time for both conditions (both p < 0.05) with differences in the time course. Discussion: Lower body immersion in extreme cold water for a short period of time was not a sufficient stimulus to induce a significant disruption of human body homeostasis: neuromuscular function was not significantly altered during a maximum intensity fatigue task.